Activin A Modulates Inflammation in Acute Pancreatitis and Strongly Predicts Severe Disease Independent of Body Mass Index. Issue 5 (1st May 2020) - Thomas, Alexandra L.; Castellanos, Karla; Mancinelli, Georgina; Xia, Yinglin; Bauer, Jessica; Yazici, Cemal; Fantuzzi, Giamila; Hwang, Rosa F.; Krett, Nancy L.; Papachristou, Georgios I.; Whitcomb, David C.; Jung, Barbara
Abstract : INTRODUCTION: Acute pancreatitis (AP) is a healthcare challenge with considerable mortality. Treatment is limited to supportive care, highlighting the need to investigate disease drivers and prognostic markers. Activin A is an established mediator of inflammatory responses, and its serum levels correlate with AP severity. We hypothesized that activin A is independent of body mass index (BMI) and is a targetable promoter of the AP inflammatory response. METHODS: We assessed whether BMI and serum activin A levels are independent markers to determine disease severity in a cohort of patients with AP. To evaluate activin A inhibition as a therapeutic, we used a cerulein-induced murine model of AP and treated mice with activin A-specific neutralizing antibody or immunoglobulin G control, both before and during the development of AP. We measured the production and release of activin A by pancreas and macrophage cell lines and observed the activation of macrophages after activin A treatment. RESULTS: BMI and activin A independently predicted severe AP in patients. Inhibiting activin A in AP mice reduced disease severity and local immune cell infiltration. Inflammatory stimulation led to activin A production and release by pancreas cells but not by macrophages. Macrophages were activated by activin A, suggesting activin A might promote inflammation in the pancreas in response to injury. DISCUSSION: Activin A provides a promising therapeutic target to interrupt the cycle of inflammation and tissue damage in AP progression. Moreover, assessing activin A and BMI in patients on hospital admission could provide important predictive measures for screening patients likely to develop severe disease.